Rekomendasi Pemilihan Produk Simpanan Tabungan Bank Menggunakan Metode Weighted Product (WP) - Agus Sidiq Purnomo; Jevi Ariyanti (INFORMAL: Informatics Journal, 2019)
Many banks in Indonesia, both public and private banks, offer different advantages to the customers. As a result, it is often difficult for the public to decide where to save their money. For this reason, the writer propose a decision support system to help recommend a bank as a smart solution for saving. This study employed the Weighted Product (WP) with seven criteria, namely initial deposit, subsequent deposits, administrative costs, depositional balances, interest rates, age range, and facilities. This system can help the prospective customers determine the ideal savings place for the future needs. This study shows that the highest final value after calculation is 0.0320 for Batara of BTN bank, and the lowest value is 0.0132 for Tapres of BCA bank.